The image in print : book illustration in late medieval England and its sources - Driver, Martha W. (British Library, 2004)
"Martha Driver here invites us to consider evidence for a new social history of book illustration as constructed from the study of the woodcut, principally as it was used in books printed in England by Wynkyn de Worde and his successors. Her central focus is on the physical evidence provided by illustrations in incunabula and early-sixteenth-century printed books. Among the subjects under consideration are reading and the development of literacy, and the central role of woodcuts in that process. In addition to promoting the self-education of their readers, illustrated printed books acted as agents of religious, social, and political change as the Middle Ages closed and the Reformation tightened its grip on western Europe. Religious devotion, marriage, work, and everyday life feature in the arresting images that illustrate the text."--Jacket.